An integrated approach for investigating geomorphic response to extreme events: methodological framework and application to the October 2011 flood in the Magra River catchment, Italy. Issue 6 (16th February 2016) - Rinaldi, Massimo; Amponsah, William; Benvenuti, Marco; Borga, Marco; Comiti, Francesco; Lucía, Ana; Marchi, Lorenzo; Nardi, Laura; Righini, Margherita; Surian, Nicola
Abstract: A high‐magnitude flash flood, which took place on 25 October 2011 in the Magra River catchment (1717 km 2 ), central‐northern Italy, is used to illustrate some aspects of the geomorphic response to the flood. An overall methodological framework is described for using interlinked observations and analyses of the geomorphic impacts of an extreme event. The following methods and analyses were carried out: (i) hydrological and hydraulic analysis of the event; (ii) sediment delivery by event landslide mapping; (iii) identification and estimation of wood recruitment, deposition, and budgeting; (iv) interpretation of morphological processes by analysing fluvial deposits; (v) remote sensing and geographic information system (GIS) analysis of channel width changes. In response to the high‐magnitude hydrological event, a large number of landslides occurred, consisting of earth flows, soil slips, and translational slides, and a large quantity of wood was recruited, in most part deriving from floodplain erosion caused by bank retreat and channel widening. The most important impact of the flood event within the valley floor was an impressive widening of the overall channel bed and the reactivation of wide portions of the pre‐event floodplain. Along the investigated (unconfined or partly confined) streams (total investigated length of 93.5 km), the channel width after the flood was up to about 20 times the channel width before the event. The study has shown that a synergic use of different methods and types of evidence provides fundamental information for characterizing and understanding the geomorphic effects of intense flood events. The prediction of geomorphic response to a flood event is still challenging and many limitations exist; however a robust geomorphological analysis can contribute to the identification of the most critical reaches. Copyright © 2016 John Wiley & Sons, Ltd.